The Effect of Applying the Teaching at the Right Level (TaRL) Approach Assisted by LKPD to Improve the Learning Outcomes of Grade 6 Elementary School Students on Electrical Circuits - Nurida Aryanti; Muthamainah (Jurnal Penelitian Pendidikan IPA, 2024)
The research aims to examine the effect of implementing the Teaching at the Right Level (TaRL) approach assisted by LKPD to improve the learning outcomes of grade 6 elementary school students on electrical circuits. The research was carried out at SDN 1 Semangkak on class VI students. The sampling technique uses a purposive area sampling method. The research used a quasi-experimental design with data collection techniques through post-tests in the form of multiple choice questions and descriptions, observation, documentation and interviews. The data obtained was analyzed using statistical tests which included normality tests, data analysis using the Paired Samples t-Test. Based on the Validity Test, the results show r = 0.82 α >(0.05) so that all question items show valid results. Reliability test if the value α > 0.738 the value is reliable, namely 0.894. Then the results of the normality test value of learning outcomes are 0.467 > α (0.05) exceed the significant value, then the variable values are normally distributed, followed by using the Paired Sample t-Test test, the test results -t is the learning result at a sig value of 0.00 < α (0.05), so reject H0. So it can be concluded that there is an influence of implementing the Teaching at the Right Level (TaRL) approach assisted by LKPD to improve the learning outcomes of Grade 6 Elementary School students on electrical circuits.